Spin Crossover, Polymorphism and Porosity to Liquid Solvent in Heteroleptic Iron(III) {Quinolylsalicylaldimine/Thiosemicarbazone‐Salicylaldimine} Complexes. Issue 4 (11th December 2015) - Phonsri, Wasinee; Davies, Casey G.; Jameson, Guy N. L.; Moubaraki, Boujemaa; Murray, Keith S.
Abstract: Heteroleptic iron(III) complexes of formula [Fe(qsal)(thsa)]⋅solvent have been synthesized: [Fe(qsal)(thsa)]⋅0.4 BuOH (1 ), [Fe(qsal)(thsa)]⋅0.5 MeCN (2 ) and [Fe(qsal)(thsa)]⋅0.5 THF, (3 ). The latter two show partial solvent loss at room temperature to yield [Fe(qsal)(thsa)]⋅0.1 MeCN (2′ ) and [Fe(qsal)(thsa)]⋅0.1 THF (3′ ), respectively. This family maintains a structural integrity which is analogous over different degrees of solvation, a rare occurrence in discrete molecular species. Uniquely, removal of MeCN from compound2 leads to retention of crystallinity yielding the isostructural, fully desolvated compound [Fe(qsal)(thsa)] (2′′ ) and a new high spin polymorph, 4 . To the best of our knowledge, this is the first compound that forms polymorphs through a desolvation process. The desolvated mixture, 2′′ and4, is porous and can reabsorb MeCN and give rise to2′ again. This illustrates the reversible single‐crystal‐to‐single‐crystal transformation of two polymorphs back to a purely original phase, 2′′ +4 ↔2′ . The structural, magnetic and Mőssbauer features of the various samples are described in terms of spin crossover. Abstract : Sign of the cross : [Fe(qsal)(thsa)]⋅solvent complexes, where solvent is MeCN or THF, have been characterized. For MeCN compounds, spin crossover properties are observed in both the solvated and non‐solvated compounds (see scheme). Interestingly, the desolvation process in [Fe(qsal)(thsa)]⋅ n  MeCN resulted in two new polymorphs of Fe III spin crossover systems, for the first time. The desolvated material is porous to liquid MeCN.